Does book-tax difference matter? An analysis of relation with earnings persistence - Rodrigues, Jomar Miranda; Pereira, Vinicius Monteiro (Revista de Contabilidade do Mestrado em Ciências Contábeis da UERJ, 2023)
In Brazil, with the accounting convergence process, the accounting standards issued by the IASB began to lead corporate accounting. However, together with the adoption of international standards, it remains in force, largely because of the Brazilian code law regime, tax rules that influence accounting procedures. The main problem is that accounting standards and tax rules have different objectives and, from this misalignment, the figure of the book-tax difference (BTD) emerges. BTD ends up influencing the results presented in the accounting reports, considering that its registration arises from conceptual differences between accounting standards and tax rules, generating temporary or permanent differences. In this scenario, it is important to know the effects of this misalignment (BTD) on the quality of earnings, especially in the attribute of earnings persistence. Therefore, the aim of this study was to identify the effects of BTD on the persistence of earnings or cash flows, based on the econometric model proposed by Dechow and Schrand (2004). For this purpose, a sample of 335 companies with observations from 2000 to 2019 was used. Among the main results, it was found that, in fact, BTD negatively influences earnings persistence, that is, the higher the BTD, the lower it tends to be the persistence of earnings. Additionally, it was found that the BTD does not have a significant influence on the persistence of cash flows. Finally, it was identified that, in the period observed, cash flows were more persistent than accounting earnings, in contrast to what was observed by Dechow (1994).